Master equation approach to protein folding - Cieplak, M.; Henkel, M.; Banavar, J.R. (Condensed Matter Physics, 1999)
The dynamics of two 12-monomer heteropolymers on the square lattice is studied exactly within the master equation approach. The time evolution of the occupancy of the native state is determined. At low temperatures, the median folding time follows the Arrhenius law and is governed by the longest relaxation time. For both good and bad folders, signiﬁcant kinetic traps appear in the folding funnel and the kinetics of the two kinds of folders are quite similar. What distinguishes between the good and bad folders are the differences in their thermodynamic stabilities. За допомогою методу керуючого рівняння точно проаналізована динаміка двох 12-мономерних гетерополімерів на квадратній гратці. Визначена часова еволюція зайнятості нативного стану. При низьких температурах середній час скручування підлягає закону Ареніуса і визначається найдовшим часом релаксації. Для білків, що добре скручуються, з’являються суттєві кінетичні пастки у наборі послідовних конформацій, у той час як для білків, що погано скручуються, пастки присутні також і в ділянках, що не відповідають нативній конформації.